IMPLEMENTATION OF GOOD GOVERNANCE IN THE PROTOCOL AND LEADERSHIP COMMUNICATIONS DIVISION OF BANDAR LAMPUNG CITY IN OFFICIAL GOVERNMENT EVENTS - Olivia Amarezha; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method is used to describe the implementation of good governance in the Protocol and Communication Division of Bandar Lampung City Leadership During Official Events. All data was obtained directly from informants in the field using interviews and document studies. The results of the study indicate that, in general, the implementation of official events has been running smoothly, but not yet fully optimal. The communication dimension has supported the coordination of leadership activities, but still requires improvement in the clarity and consistency of information. The resource dimension indicates efforts to meet the needs of apparatus and work facilities, but this is not fully supported by adequate competence and facilities. In terms of disposition or attitude of implementers, some apparatus have demonstrated commitment and professionalism, although there are still differences in levels of discipline and responsibility. Meanwhile, the dimensions of the bureaucratic structure have provided a framework for task implementation, but still face challenges in flexibility and effective coordination.